An investigation of defamilization/familization measures to assist women to save pension income and strengthen the adult worker model—The case of Hong Kong. Issue 3 (12th September 2017) - Yu, Sam W. K.; Foster, Liam; Chau, Ruby C. M.; Lee, Anna M. Y.
Abstract : This paper examines the use of defamilization and familization measures to develop an analytical framework to inform the search for ways to improve women's opportunities to accumulate pension income. This framework is associated with the use of the adult worker model. Three main analytical tasks are presented. Firstly, we discuss different interpretations of what defamilization entails. Based on these different views, two types of defamilization measures utilized by the government are identified: care‐focused and economic defamilization. Secondly, with reference to different definitions of the adult worker model, we develop a framework for identifying ways to make the provision of the government's defamilization measures and its alternatives (care‐focused and economic familization measures) more effective in assisting women to accumulate pension income. Thirdly, using the case of Hong Kong, we demonstrate the application of this analytical framework.